The Implementation of Group Discussion Method to Improve Social Studies (IPS) Learning Outcomes of Fourth-Grade Students at SD Plus Melati Samarinda - Siti Rabiatul Adawiyah; Romdhiatin Nafi’ah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the application of the group discussion method with Matching Card media and to improve social studies (IPS) learning outcomes of fourth grade students at SD Plus Melati Samarinda. The background of this research is the low learning outcomes of IPS students, where only 8 out of 20 students (40%) achieved the minimum competency score (KKM) of 75 in the pre-cycle. This study used a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects were 20 fourth grade students of SD Plus Melati Samarinda in the 2024/2025 academic year. The results showed significant improvement: the class average score increased from 66.65 in the pre-cycle to 77.75 in Cycle I, and 85.55 in Cycle II. Classical learning completeness increased from 40% to 70% in Cycle I, and reached 100% in Cycle II. The group discussion learning method was evaluated as effective, as it successfully encouraged student activity, collaboration, and comprehensive understanding of IPS material. This research concludes that the group discussion method assisted by Matching Card media is proven effective in improving IPS learning outcomes of fourth grade students at SD Plus Melati Samarinda.